2017
DOI: 10.1002/jsfa.8610
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulants from food processing by‐products: agronomic, quality and metabolic impacts on organic tomato (Solanum lycopersicum L.)

Abstract: The results were indicative of the biostimulant activity of these extracts and demonstrated them, particularly FPR, as promising candidates for enhancing plant productivity and fruit quality. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 50 publications
10
35
0
Order By: Relevance
“…Higher content of reduced AsA was observed in all the genotypes and of total AsA in the genotypes E17 and PDVIT. This result confirms data previously obtained in other studies that demonstrated an increase in AsA content in tomato, in kiwi fruits and in peppers after the application of plant-based biostimulants [36,41]. Contrary to what seen in the leaf, the content of total phenols in berries of treated E17 and E36 genotypes was higher compared to the non-treated control.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Higher content of reduced AsA was observed in all the genotypes and of total AsA in the genotypes E17 and PDVIT. This result confirms data previously obtained in other studies that demonstrated an increase in AsA content in tomato, in kiwi fruits and in peppers after the application of plant-based biostimulants [36,41]. Contrary to what seen in the leaf, the content of total phenols in berries of treated E17 and E36 genotypes was higher compared to the non-treated control.…”
Section: Discussionsupporting
confidence: 92%
“…Assessing the content of lipophilic antioxidants, the treatment with the biostimulant had no effects on the content of carotenoids and chlorophylls but only on the total lipophilic antioxidant activity. Similar results were obtained by Chehade et al [36] in tomato. On the contrary, Rouphael et al [41] demonstrated that in tomato foliar applications of a legume-derived protein hydrolysate had an effect also on lycopene content.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the "Global Biostimulants Market 2019-2027", the global market for biostimulants has been projected to reach $625.67 billion by 2027. The biostimulants improve the nitrogen metabolism, influence the modulation of cell metabolism, control the transfer of nutrients, supervise the lipid biosynthesis, and regulate the stimulation of the soil microbial activity and the root growth [3,4]. Some researchers ascribe their protective effect to the activation of the antioxidant defense system of plants and the production of the phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%